2013
DOI: 10.1039/c3em00224a
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial disposal by incineration

Abstract: As nanotechnology-based products enter into widespread use, nanomaterials will end up in disposal waste streams that are ultimately discharged to the environment. One possible end-of-life scenario is incineration. This review attempts to ascertain the potential pathways by which nanomaterials may enter incinerator waste streams and the fate of these nanomaterials during the incineration process. Although the literature on incineration of nanomaterials is scarce, results from studies of their behavior at high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 82 publications
0
33
1
Order By: Relevance
“…The furnace temperature was fixed at 950°C, and the temperature in the lab-scale incineration reactor was measured with a thermocouple placed near the crucible. The chosen temperatures falls in the range of 850-1200°C, which are typical combustion temperatures of a full-scale incineration plant (Holder et al, 2013). During the experiments the air inlet was adjusted at 3 l/min, in accordance with the ISO 19011 (ISO, 2011).…”
Section: Lab Scale Incineration Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The furnace temperature was fixed at 950°C, and the temperature in the lab-scale incineration reactor was measured with a thermocouple placed near the crucible. The chosen temperatures falls in the range of 850-1200°C, which are typical combustion temperatures of a full-scale incineration plant (Holder et al, 2013). During the experiments the air inlet was adjusted at 3 l/min, in accordance with the ISO 19011 (ISO, 2011).…”
Section: Lab Scale Incineration Testmentioning
confidence: 99%
“…nanowaste). However, very limited information and experimental data are available concerning the fate of ENPs during waste treatment (Holder et al, 2013). According to Bystrzejewska-Piotrowska et al (2009) and Moore (2006), the impact of nano-based products introduced to the market should be addressed before waste containing ENPs appears in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that silica, titanium, alumina, iron and zinc oxides dominated the ENM market in 2010 based on material mass flow analysis. Among these ENMs, zinc oxide (ZnO), the focus of this study, is commonly used in cosmetics, electronic and optics, Even though various studies predict that the majority of ENMs will end up in landfills either through direct disposal or as sludge and bottom and fly ash matrix from waste incineration [2,[6][7][8][9], information about the fate of ENMs during waste stabilization is still scarce [10]. It is however reported that future research activities should at least include analytical techniques to characterize nano-waste, definition of acceptable limit values for exposure and to determine the release mechanisms of ENMs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is a need to develop research in the scope of nanowaste treatment and to reduce the unintentional release into the environment. But the lack of adequate tools and methods to measure emissions of nanoparticles accurately and significant gaps in data, monitoring, and technology hinder the precise determination of nanoparticle emissions [5]. From the other hand, governments have to take a proactive approach towards developing a waste strategy for nanomaterials, for prevention against long-term unintended consequences.…”
Section: Nanowastementioning
confidence: 99%
“…Manufactures ENMs comprise seven main classes: carbonaceous nanomaterials (e.g., carbon nanotubes); semiconductors (e.g., quantum dots); metal oxides (e.g., zinc oxide); nanopolymers (e.g., dendrimers); nanoclays; emulsions (e.g., acrylic latex); and metals (e.g., silver). Except for carbon black, the TiO 2 nanomaterial is produced most often; in order of most to least produced ENMs, TiO 2 >SiO 2 >ZnO>Fe and FeOx>Al 2 O 3 >CeO 2 >CNT>Ag [1,5,6]. It should be noted that the nanomaterials can be released to the environment at any stage of the life cycle of products (LCA -Life Cycle Assessment), from the manufacture, use, and disposal or recycling processes.…”
Section: Introductionmentioning
confidence: 99%